ANALISIS POLITIK HUKUM TERHADAP PENERAPAN ASAS KEADILAN DALAM HUKUM ISLAM DI INDONESIA - Delvi Salwa Nakita; Syah Wardi (Sharia Law and Justice Journal, 2025)
This study examines the political aspects of law in the application of the principle of justice to Islamic law, with the aim of analyzing the extent to which the principles that are sometimes in Islamic law can be applied in legal politics. In this study, the author uses a qualitative approach using the literature study method. The results of the study indicate that there are several political legal challenges to the application of this principle of justice and the public's understanding of Islamic law is still minimal. In addition, this study also finds a solution to this problem by creating a more focused framework for the values of justice contained in Islamic law, thus social justice for the entire community can be realized. This study is expected to provide learning for legal science developers, especially in understanding between politics and law in Islamic justice.